2022
DOI: 10.1136/jitc-2021-003752
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-based redirection of universal Fabrack-CAR T cells selectively kill antigen bearing tumor cells

Abstract: BackgroundChimeric antigen receptor (CAR) T cells engineered to recognize and target tumor associated antigens have made a profound impact on the quality of life for many patients with cancer. However, tumor heterogeneity and intratumoral immune suppression reduce the efficacy of this approach, allowing for tumor cells devoid of the target antigen to seed disease recurrence. Here, we address the complexity of tumor heterogeneity by developing a universal CAR.MethodWe constructed a universal Fabrack-CAR with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previously, we demonstrated that this meditope-binding site is absent in human mAbs but can be readily grafted onto them; we termed the constructs meditope-enabled Abs (memAbs). We have demonstrated that the presence of the meditope does not affect antigen binding of memAbs (35)(36)(37)(38). Here, we used the technology, in concert with qSMLM, to determine how the clustering of HER2 was affected by the valency.…”
Section: Clustering Of Her2 Increases Upon Treatment With Multivalent...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that this meditope-binding site is absent in human mAbs but can be readily grafted onto them; we termed the constructs meditope-enabled Abs (memAbs). We have demonstrated that the presence of the meditope does not affect antigen binding of memAbs (35)(36)(37)(38). Here, we used the technology, in concert with qSMLM, to determine how the clustering of HER2 was affected by the valency.…”
Section: Clustering Of Her2 Increases Upon Treatment With Multivalent...mentioning
confidence: 99%
“…This site has also been engineered into other mAbs which we have named meditopeenabled mAbs (memAbs) (34). MemAbs retain their affinity, selectivity, and function (35)(36)(37)(38). Importantly, this technology allows us to add unique functionality to mAbs, including "noncovalent crosslinking" through multivalent meditopes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the safety‐switch mechanism TM123 redirected uni‐CAR‐T and allowed to obtain reversible toxicity in a mouse model. Proposed by Kuo et al 65 universal Fabrack‐CAR‐T, using the meditope technology, contained the meditope peptide as a tumor targeting domain, making them effective in a broad range of tumors, including CD33 expressing. A further challenge with uni‐CAR‐T is their poorer survival rate, which can be addressed by reducing their immunogenicity 66 .…”
Section: The Potential Of Personalized Allo‐car‐tmentioning
confidence: 99%